2022
DOI: 10.1097/bpb.0000000000000963
|View full text |Cite
|
Sign up to set email alerts
|

Fractures of the proximal segments of the pediatric distal radial metaphysis exhibit less angular stability than fractures of the distal segments

Abstract: The distal part of the forearm is divided into the physis, metaphysis, diaphyseal metaphyseal junction (DMJ) and diaphysis. The treatment of radial DMJ fractures is challenging because this region has diaphyseal characteristics. We speculated that the stability of metaphyseal fractures could vary depending on their proximity to the DMJ or physis. Our study aimed to investigate the stability of pediatric distal radius fractures in the physis, metaphysis and DMJ. Ninety-five patients were classified into three g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…As a result of the study of Tarr et al [ 19 ], they observed a 13% loss of forearm rotation in patients who recovered with more than 10 degrees of angulation. In their study, Sato et al [ 8 ] considered angulation more significant than 10 degrees after surgery as a malunion that affects clinical results. In our research, angulation of more than 10 degrees was not observed in any cases in which ESIN was applied with the poller K-wire, and the forearm rotation limitation of the patients improved below 10%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As a result of the study of Tarr et al [ 19 ], they observed a 13% loss of forearm rotation in patients who recovered with more than 10 degrees of angulation. In their study, Sato et al [ 8 ] considered angulation more significant than 10 degrees after surgery as a malunion that affects clinical results. In our research, angulation of more than 10 degrees was not observed in any cases in which ESIN was applied with the poller K-wire, and the forearm rotation limitation of the patients improved below 10%.…”
Section: Discussionmentioning
confidence: 99%
“…Lieber et al defined a fracture application that remains too distal for K-wire application and too proximal for ESIN application for fractures in the DRDJM region [ 9 ]. Reduction losses were observed in the follow-ups due to insufficient K-wire fixation of fractures due to applications with very high angles to the fracture [ 8 ]. Transepiphyseal intramedullary applications have been described previously due to the difficulty of applying ESIN and the inability to obtain proper alignment [ 4 , 9 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence of fracture reduction quality, fixation stability, and complications for this technique is sparse, however. In addition, recent biomechanical studies have shown differing levels of stability in distal radius fractures involving the physis versus purely metaphyseal fractures [ 11 ].…”
Section: Introductionmentioning
confidence: 99%